2018
DOI: 10.12816/0049759
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status among 9 Years Old School Children in Al-Diwaniyah City, Iraq

Abstract: Background: Although they are not life threatening, dental caries and periodontal disease are the most predominant and widely spread oral diseases throughout the world. Another most common dental problem seen in children is dental trauma. The aims of the study included the investigation of the prevalence and severity of dental caries, gingivitis and dental plaque in relation to gender, furthermore, the prevalence and severity of the traumatized anterior teeth were assessed. Materials and Methods: This oral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…The result reflected the presence of poor oral hygiene among the rural children, which could be due to the low awareness level and the less use of oral hygiene aids in rural area than the urban one (27) . In present study, there was no significant difference between boys and girls concerning of plaque index and this was in agreement with other studies (12)(13)(14)(15) . However, other studies (8,23.28-34,12) found that boys had statistically higher plaque index than girls.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The result reflected the presence of poor oral hygiene among the rural children, which could be due to the low awareness level and the less use of oral hygiene aids in rural area than the urban one (27) . In present study, there was no significant difference between boys and girls concerning of plaque index and this was in agreement with other studies (12)(13)(14)(15) . However, other studies (8,23.28-34,12) found that boys had statistically higher plaque index than girls.…”
Section: Discussionsupporting
confidence: 94%
“…This difference could be due to the effect of many factors like; diet, oral hygiene, age, secretion of salivary gland could be effect on the amount of dental plaque, therefor the amount of plaque was vary among the individuals (4,35,36) . Result in this study showed that the prevalence of gingivitis was lower than that reported by previous Iraqi studies (11,12,15) . It was assured that dental plaque is the main etiological factor for gingivitis (37).…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations